(Doda Idi) Vokabuler Aceh yang Terlupakan - Dharminta Soeryana (Ekspresi Seni : Jurnal Ilmu Pengetahuan dan Karya Seni, 2011)
The development and growth of healthy children is inseparable from the success of a mother to and mentally, one through a child a bedtime song. Humming lullabies to a child is one of the heritages of cultural activities that is inherited by the preceding generation to the next generation to preserve to this day. Chanting poetry which contains advice, teaching points, values and principles of life to child will be useful for the child‟s development.